Diagnostic Dilemma of Disseminated Histoplasmosis Mimicking Hemophagocytosis Lymphohistiocytosis in Patient with Rheumatoid Arthritis on Anti-TNF Therapy: Case Report and Review of the Literature - Saurav Suman; Aleksander Lenert (Case Reports in Rheumatology)
Tumor necrosis factor inhibitors (TNFi) have become the cornerstone for the treatment of rheumatoid arthritis and other systemic autoimmune conditions. However, these biologic DMARDs can lead to various opportunistic infections such as viral infection, tuberculosis, and histoplasmosis. Furthermore, these biologics can also cause severe systemic inflammatory reactions known as hemophagocytosis lymphohistiocytosis (HLH) that can lead to multiorgan failure and high mortality. Due to overlapping clinical features and time-intensive microbiological culture methods, distinguishing between HLH and opportunistic infections can be challenging early in the disease course. We present a similar situation with our patient where the patient met the diagnostic criteria for HLH however was found to have disseminated histoplasmosis. This case uniquely evaluates the utility of the HLH diagnostic criteria and hemophagocytosis for accurate diagnosis of HLH.